How Does Government Policy Improve Green Technology Innovation: An Empirical Study in China - Wu, Guancen; Xu, Qian; Niu, Xing; Tao, Li (Frontiers in Environmental Science, 2022)
Government policies have an increasingly important role in green technological innovation. This paper divides government policy according to policy quantity, policy effectiveness and policy executive force so that the government policy can be quantified in more detail. Green patent data is used to characterize green technological innovation, and the fixed effect model is used to analyze panel data analysis from 2010 to 2019. The empirical results show that: (1) the direct effect of policy on green technology innovation is promotion and significant; (2) the impact of policy quantity and policy effectiveness on green technology innovation is greater than that of policy executive force; (3) the impact of policy on industry-university-research cooperation for green technology innovation is still uncertain; (4) green technology innovation policy will weaken the stimulating effect of enterprise innovation vitality. Research conclusions show that the direct and indirect effects of government policies on green technology innovation are heterogeneous. The government still needs to appropriately increase policy quantity, policy effectiveness, and executive force, improve the industry-university-research cooperation system for green technology, and accelerate the establishment of market-oriented green technology innovation environment.